Criminological aspects of rape - Siniša Franjić (Forensic Science Today - Peertechz Publications, 2021)
Rape is a type of sexual assault that usually involves sexual intercourse or another form of sexual penetration without the consent of the victim. The act can be committed by physical force, threat and abuse of power. The act may also be committed against a person who is unable to give valid consent, such as one who is unconscious, disabled, has intellectual disabilities or is a juvenile.